Antipsychotics can induce pre‐shock in very elderly patients: a report of two cases. Issue 1 (27th April 2015) - Ueda, Satoshi; Omori, Ataru; Shioya, Touko; Okubo, Yoshiro
Abstract: Antipsychotics have often been administered to treat delirium and intractable insomnia in elderly patients with or without dementia. However, antipsychotics sometimes cause severe adverse effects. We report two cases of very elderly patients who developed pre‐shock after the administration of antipsychotics in a clinical consultation‐liaison setting. These cases suggest that antipsychotics can induce fatal adverse events in very elderly patients. Although there has been little evidence regarding the most appropriate kind of drug and dosage for such patients, psychiatrists should exercise great caution in the use of antipsychotics for the very elderly, including deciding to prescribe the lowest dose or not prescribing them at all.